ASSOCIATION OF HUMAN CHORIONIC GONADOTROPHIN WITH PREGNANCY INDUCED HYPERTENSION: beta HCG and pregnancy induced hypertension - Chatha, Nayab Afzal; Jaffery, Humaira Osman; Qamar, Saima; Mustafa, Nilofar; Kamran, Rizwana; Ashraf, Viqar (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the positive predictive value of beta Human Chorionic Gonadotrophin in early secondtrimester for predicting pregnancy induced hypertension.Study Design: Cross-sectional study.Place and Duration of Study: Department of Obstetrics and Gynaecology Combined Military Hospital, Lahore,from Jun 2017 to Nov 2017.Methodology: A total of 214 female pregnant patients met the criteria for inclusion in this study. Patients withbeta human chorionic gonadotrophin (βHcg) levels ≥2 MoM were followed at 22, 26, 30 and 34 weeks of gestation. Blood pressure was monitored. Pregnancy induced hypertension (PIH) was labelled after 20 weeks (as per dating scan) of gestation in patients who did not have proteinuria (≥300 mg 24 hour urine sample) and had a systolic blood pressure ≥140 mmHg and/or a diastolic blood pressure ≥90 mmHg (blood pressure readings taken at two separate points in time four hours apart).Results: Patients ranged between 18-35 years of age, with the mean age being 27.3 ± 4.3 years. Mean gestational age was observed to be 15.6 ± 1.8 weeks. Mean BMI was 23.8 ± 3.2 kg/m2. Out of 214 patients, 30 patients (14%) had beta human chorionic gonadotrophin level >2 MoM. Out of these 30 patients, 25 patients (83.3%) developed PIH. There were 100 primigravida (46.7%) and 114 multigravidas (53.3%). Beta human chorionic gonadotrophin in predicting pregnancy induced hypertension showed sensi-tivity of 96.1%, a specificity of 97.3%, with a PPV83.3%, a NPV 99.4% and diagnostic accuracy of 97.2%.